2019
DOI: 10.1002/fam.2756
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on the effects of naturally ventilated shaft and fire locations in urban tunnels

Abstract: Summary In more and more tunnels, natural ventilation mode with vertical shafts has been gradually employed. However, there are few studies investigating the influences of fire and shaft positions on natural ventilation performance currently. Therefore, this study investigated the effects of the transverse distance from fire source to tunnel sidewall, the longitudinal distance from fire source to shaft, and the transverse distance from shaft to sidewall on natural ventilation effectiveness in a tunnel fire by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…Huang et al 20 used three cable trays with different cable layouts to conduct fire tests in a closed room and studied the combustion behavior of cable trays on the wall. Fan et al 21 investigated the effects of the transverse distance from fire source to tunnel sidewall, the longitudinal distance from fire source to the shaft, and the transverse distance from the shaft to sidewall on natural ventilation effectiveness in a tunnel fire by using Fire Dynamics Simulator. The typical characteristic parameters of smoke, such as mass flow rate, temperature distribution, and velocity vector were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al 20 used three cable trays with different cable layouts to conduct fire tests in a closed room and studied the combustion behavior of cable trays on the wall. Fan et al 21 investigated the effects of the transverse distance from fire source to tunnel sidewall, the longitudinal distance from fire source to the shaft, and the transverse distance from the shaft to sidewall on natural ventilation effectiveness in a tunnel fire by using Fire Dynamics Simulator. The typical characteristic parameters of smoke, such as mass flow rate, temperature distribution, and velocity vector were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The releasing soot from combustion may result in accidental death. [1][2][3] The burning of biomass and fossil fuels emits substantial amounts of particle matter that impacts on public health, reduces air visibility thereby resulting in accidents and economic losses, and even has a significant impact on global climate change. 4,5 The luminous soot can also enhance the radiation from flames.…”
Section: Introductionmentioning
confidence: 99%
“…The soot is generated from combustion process which provides the primary sources of energy. The releasing soot from combustion may result in accidental death 1‐3 . The burning of biomass and fossil fuels emits substantial amounts of particle matter that impacts on public health, reduces air visibility thereby resulting in accidents and economic losses, and even has a significant impact on global climate change 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various scholars have studied the impact of height, cross-sectional area, distance from the combustion source, inclination, quantity, and other parameters of the upper vent on the smoke exhaust of the upper vent using a combination of theoretical analysis and numerical simulation. They found that a large cross-sectional area of the upper vent and a longer longitudinal distance from the combustion source contribute more favorably to flue gas emission than the height of the vent, which has a limited contribution [13][14][15]. Moreover, an upper vent that is low in position and slightly inclined can enhance emission efficiency, the best inclination being 76 • [16].…”
Section: Introductionmentioning
confidence: 99%